Iridium containing catalyst for water electrolysis
By uniformly distributing iridium oxide and other substances on the support material to form a thin layer of catalyst, the problems of inefficient oxygen generation reaction and low iridium use efficiency in water electrolysis are solved, and an efficient and sustainable water electrolysis process is achieved.
Patent Information
- Application Number
- JP2023533658
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-23
- Filing Date
- 2021-12-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-12-22
AI Technical Summary
In the existing water electrolysis method, the oxygen generation reaction exhibits low efficiency under the anode, requires high overvoltage, and the efficiency of catalysts is not high due to the limitations of the anode material, especially the efficiency and sustainability of precious metal catalysts such as iridium are limited.
By uniformly distributing iridium oxide, iridium hydroxide, or mixtures thereof on the support material, a catalyst thin layer with an average layer thickness of up to 50% iridium content in the range of 1.5 nm to 5.0 nm is formed, combining a support material with a high surface area to reduce the amount of iridium use.
It is achieved that high oxygen generation reaction activity is maintained under low iridium loading, the iridium package density of the anode layer is reduced, and the efficiency and sustainability of the water electrolysis method are improved.
Smart Images

Figure 0007660679000004 
Figure 0007660679000005 
Figure 0007660679000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an iridium-containing catalyst for the oxygen evolution reaction in water electrolysis.
[0002] Hydrogen is considered to be the energy carrier of the future as it allows for sustainable energy storage, is available over long periods of time and can also be produced using regenerative energy techniques.
[0003] Steam reforming is currently the most common method for producing hydrogen. In steam reforming, methane and steam are reacted to produce hydrogen and CO. Water electrolysis represents a further variant of hydrogen production. High purity hydrogen can be obtained via water electrolysis.
[0004] There are various methods of water electrolysis, notably alkaline water electrolysis, acid water electrolysis using a polymer electrolyte membrane ("PEM", PEM water electrolysis), and high temperature solid oxide electrolysis.
[0005] A water electrolysis cell contains a half-cell with an electrode where the oxygen evolution reaction (OER) takes place, and a further half-cell with an electrode where the hydrogen evolution reaction (HER) takes place. The electrode where the oxygen evolution reaction takes place is called the anode.
[0006] An overview of water electrolysis technology, and in particular PEM water electrolysis, can be found, for example, in M. Carmo et al., International Journal of Hydrogen Energy, 38, 2013, pp. 4901-4934, and V. Himabindu et al., Materials Science for Energy Technologies, 2, 2019, pp. 442-454.
[0007] In a polymer electrolyte membrane water electrolysis cell (hereinafter also referred to as a PEM water electrolysis cell), a polymer membrane serves as a proton transport medium and electrically insulates the electrodes from each other. Catalyst compositions for the oxygen evolution reaction and the hydrogen evolution reaction are applied, for example, as the anode and cathode to the front and rear surfaces of a membrane ("catalyst coated membrane CCM"), thereby obtaining a membrane electrode assembly ("MEA").
[0008] The oxygen evolution reaction occurring at the anode of a PEM water electrolysis cell can be represented by the following reaction equation: 2H2O→4H + +O2+4e -
[0009] Due to its complex reaction mechanism, the oxygen evolution reaction exhibits slow reaction kinetics, which is why significant overpotentials at the anode are required to achieve sufficiently high conversion rates. In addition, the oxygen evolution reaction proceeds under highly acidic conditions (i.e., low pH).
[0010] Efficient operation of a water electrolysis cell requires the presence of a catalyst. Since the oxygen evolution reaction at the anode proceeds under highly corrosive conditions (low pH, significant overpotential), suitable catalytic materials are especially noble metals such as ruthenium and iridium and their oxides.
[0011] A catalytically active metal or metal oxide may optionally be present on the support material to increase the specific surface area of the catalytic material.
[0012] In the case of support materials too, only those with sufficiently high stability under the highly corrosive conditions of the oxygen evolution reaction are suitable, for example transition metal oxides such as TiO2 or oxides of certain main group elements such as Al2O3. However, many of these oxide-based support materials are non-conductive, which has a detrimental effect on the efficiency of the oxygen evolution reaction and therefore also on the efficiency of water electrolysis.
[0013] An overview of catalysts for the oxygen evolution reaction under acidic conditions (i.e. at the anode of a PEM water electrolysis cell) can be found, for example, in P. Strasser et al., Adv. Energy Mater., 7, 2017, 1601275, and FM Sapountzi et al., Progress in Energy and Combustion Science, 58, 2017, pp. 1-35.
[0014] WO 2005 / 049199(A1) describes a catalyst composition for the oxygen evolution reaction in PEM water electrolysis. The catalyst contains iridium oxide and an inorganic oxide acting as a support material. The support material is 50 ml of iridium oxide. 2 / g~400m 2 / g and is present in the composition in an amount of less than 20 wt.%. Thus, the catalyst composition comprises a high iridium content.
[0015] Iridium reserves are very limited. M. Bernt et al., “Analysis of Voltage Losses in PEM Water Electrolyzers with Low Platinum Group Metal Loadings”, J. Electrochem. Soc. 165, 2018, F305-F314, and M. Bernt et al., “Current Challenges in Catalyst Development for PEM Water Electrolyzers”, Chem. Ing. Tech., 2020, 92, no. 1-2, pp. 31-39, state that the current typical loading of iridium on the anode side of a catalyst-coated membrane is about 1 cm of the membrane surface. 2 It has been stated that the loading is approximately 2 mg of iridium per sintered body, but that this loading must still be significantly reduced to allow large-scale use of PEM electrolysis based on the amount of iridium available.
[0016] M. Bernt et al., J. Electrochem. Soc. 165, 2018, F305-F314, describe the preparation of a catalyst-coated membrane using a commercial catalyst composition comprising TiO2-supported IrO2. The catalyst composition contains iridium (in the form of IrO2) in an amount of 75% by weight. In order to obtain an anode with the lowest possible surface-based iridium loading, the layer thickness of the anode was reduced. Membrane 1 cm 2 Iridium nanoparticles with surface loadings ranging from 0.20 mg to 5.41 mg of iridium per cm were produced and tested for their efficiency in water electrolysis. 2 Loadings of 1 mg to 2 mg of iridium per cm of membrane still gave good results, but 2 At an iridium loading of less than 0.5 mg per cm2, the anode layer thickness was thin, resulting in non-uniform electrode layers, which significantly deteriorated the efficiency of water electrolysis. Therefore, this publication changes the structure or morphology of the catalyst composition to reduce the iridium packing density in the anode layer, thereby increasing the iridium packing density per cm2 of the coating surface for the same anode layer thickness (e.g., 4 μm to 8 μm). 2 It is proposed to achieve a reduced iridium loading of less than 0.5 mg of iridium per 1000 g of sintered glass.
[0017] M. Bernt et al., Chem. Ing. Tech., 2020, 92, no. 1-2, pp. 31-39, describe that a possible approach to reduce the iridium packing density in the anode consists in using a support material with a high specific surface area (i.e., a high BET surface area) and dispersing the catalytically active metal iridium or iridium oxide as finely as possible on this support material. In this connection, the publication describes that many of the usual support materials with sufficiently high stability, such as TiO2, are non-conductive, and therefore a relatively large amount of Ir or IrO2 (>40 wt.%) is required in the catalyst composition in order to generate a network of Ir or IrO2 nanoparticles as close as possible on the surface of the non-conductive support material. The publication also describes that, as a possible approach to solving this, iridium oxide can be dispersed on a conductive support material, such as antimony-doped tin oxide.
[0018] EP 2608297(A1) describes a catalytic composition for water electrolysis containing an inorganic oxide acting as a support material and iridium oxide dispersed on the support material. The oxide-based support material is present in the composition in an amount of 25% to 70% by weight, and the iridium oxide is 30% by weight. 2 / g~200m 2 / g range of BET surface areas.
[0019] C. Van Pham et al., Applied Catalysis B: Environmental, 269, 2020, 118762, describe a catalyst for the oxygen evolution reaction of water electrolysis, comprising a core-shell structure in which TiO2 forms the core and IrO2 forms the shell. The core-shell particles contain 50 wt% IrO2. Using X-ray diffraction and the Scherrer equation, an average crystallite size of 10 nm is determined for the IrO2 shell. Catalyst-coated membranes are fabricated and the anodes are fabricated using a 1 cm2 membrane. 2 1.2 mg of iridium per cm of membrane 2 The surface based iridium loading is 0.4 mg iridium per 1000 μm.
[0020] EP 2608298 A1 describes a catalyst comprising (i) a support material having a core-shell structure and (ii) metal nanoparticles dispersed on the core-shell support. This catalyst composition is used in a fuel cell.
[0021] The object of the present invention is to provide a catalyst for the oxygen evolution reaction in acid water electrolysis ("PEM water electrolysis"), whereby an anode in a membrane electrode unit can be manufactured, said anode having as low a surface-based iridium loading as possible (i.e. as low as possible per cm of membrane 2 The catalyst has the lowest possible amount of iridium per unit area, yet is highly active for the oxygen evolution reaction.
[0022] According to a first aspect of the present invention, the above object is achieved by: a carrier material, an iridium-containing coating which is provided on a support material and which contains iridium oxide, iridium hydroxide or iridium oxide hydroxide or a mixture of at least two of these iridium compounds and has an average layer thickness in the range of 1.5 nm to 5.0 nm; A granular catalyst comprising: The catalyst comprises an iridium content of up to 50% by weight. This is achieved by a granular catalyst.
[0023] The catalyst according to the invention contains relatively small amounts of iridium (up to 50% by weight), which is present in the form of a coating on the particulate support material as iridium oxide, iridium hydroxide or iridium oxide hydroxide. In relation to the first aspect of the invention, very low surface-based iridium loadings (e.g. less than 1 cm) are possible when the average layer thickness of this iridium-containing coating on the particles of support material is in the range of 1.5 nm to 5.0 nm. 2It has been found that catalysts are obtained with which anodes can be produced that have a low iridium content (less than 0.4 mg iridium per 1000 g) and still show high activity with respect to the oxygen evolution reaction. The layer thickness can be adjusted by the amount of iridium oxide, iridium hydroxide or iridium oxide hydroxide deposited on the support material and by the BET surface area of the support material. The higher the BET surface area of the support material for a given amount of applied iridium oxide, iridium hydroxide or iridium oxide hydroxide, the smaller the layer thickness of the iridium-containing coating.
[0024] The iridium-containing coating preferably has a relatively uniform layer thickness. For example, the average layer thickness varies locally by a factor of at most two. The relative standard deviation from the average layer thickness is preferably at most 35%. As is commonly known, the relative standard deviation SD, sometimes also called the coefficient of variation, rel (%) is given by the following relationship: SD rel = [SD / M] × 100 (In the formula, M is the average value of the measured variable, i.e., the average layer thickness, in this case expressed in nm, SD is the standard deviation from the mean layer thickness, expressed in nm).
[0025] The (absolute) standard deviation, as is known, is given by the square root of the variance.
[0026] According to a second aspect of the present invention, the above object is achieved by a carrier material, an iridium-containing coating provided on a support material and containing iridium oxide, iridium hydroxide or iridium oxide hydroxide; A granular catalyst comprising: The carrier material is 2m 2 / g~50m 2 / g, and the iridium content of the catalyst is in the range of: (1.505(g / m 2 )×BET) / (1+0.0176(g / m 2)×BET)≦Ir-G≦(4.012(g / m 2 )×BET) / (1+0.0468(g / m 2 )×BET) (In the formula, BET is m 2 is the BET surface area of the support material expressed in units of .mu.m / g, Ir-G is the iridium content of the catalyst, expressed in wt.% This is achieved by using a granular catalyst.
[0027] Relatively low BET surface area (up to 50 m 2 The use of a support material having a 100% iridium content of 10 m / g makes it possible to reduce the iridium content of the catalyst. In the context of the present invention, it has surprisingly been found that an improved compromise between the lowest possible iridium content and the highest possible activity with respect to the oxygen evolution reaction can be achieved if the iridium content of the catalyst is matched to the BET surface area of the support material such that the above-mentioned conditions are met. For example, 2 If a support material with a BET surface area of 1000 nm / g is used, this means that, using the conditions described above, an iridium content in the range of 13 wt.% to 27 wt.% should be selected for the catalyst.
[0028] Unless otherwise indicated, the following description applies to both the catalyst according to the first aspect and the catalyst according to the second aspect of the invention.
[0029] The catalyst preferably does not contain any metallic iridium (i.e., iridium in the zero oxidation state). Iridium is preferably present exclusively as iridium in the +3 oxidation state (iridium (III)) and / or iridium in the +4 oxidation state (iridium (IV)). The oxidation state of iridium, and therefore the absence of iridium (0) and the presence of iridium (III) and / or iridium (IV), can be verified by XPS (X-ray photoelectron spectroscopy).
[0030] The catalyst preferably comprises iridium in an amount of up to 40% by weight, more preferably up to 35% by weight, for example the catalyst contains iridium in an amount of 5% to 40% by weight, more preferably 5% to 35% by weight.
[0031] The iridium-containing coating preferably has an average thickness in the range of 1.5 nm to 4.0 nm, more preferably 1.7 nm to 3.5 nm.
[0032] In one exemplary embodiment, the iridium-containing coating has an average thickness in the range of 1.7 nm to 3.5 nm, and the iridium content of the catalyst is up to 40% by weight.
[0033] The BET surface area of the support material is preferably greater than 2 m 2 / g~40m 2 / g, more preferably 2m 2 / g~<10m 2 / g, and even more preferably 2m 2 / g~9m 2 / g.
[0034] In a preferred embodiment, the iridium content of the catalyst satisfies the following conditions: (1.705(g / m 2 )×BET) / (1+0.0199(g / m 2 )×BET)≦Ir-G≦(3.511(g / m 2 )×BET) / (1+0.0410(g / m 2 )×BET) (In the formula, BET is m 2 is the BET surface area of the support material expressed in units of .mu.m / g, Ir-G is the iridium content of the catalyst, expressed in wt.% This is achieved by using a granular catalyst.
[0035] Even more preferably, the iridium content of the catalyst satisfies the following conditions: (1.805(g / m 2 )×BET) / (1+0.0211(g / m 2)×BET)≦Ir-G≦(3.009(g / m 2 )×BET) / (1+0.0351(g / m 2 )×BET) (In the formula, BET is m 2 is the BET surface area of the support material expressed in units of .mu.m / g, Ir-G is the iridium content of the catalyst, expressed in wt.% This is achieved by using a granular catalyst.
[0036] The iridium-containing coating preferably comprises iridium oxide hydroxide, which in addition to the oxide anion also contains the hydroxide anion and can be represented, for example, by the following formula: IrO(OH)x, where 1≦x<2.
[0037] For example, in the iridium-containing coating, the atomic ratio of iridium (IV) to iridium (III) determined by X-ray photoelectron spectroscopy (XPS) is at most 4.7 / 1.0. For example, the iridium (IV) / iridium (III) atomic ratio in the iridium-containing layer is in the range of 1.0 / 1.0 to 4.7 / 1.0. This allows the electrochemical activity of the catalyst to be further improved. In order to achieve an advantageous compromise between high electrochemical activity and high electrical conductivity, it may be preferred that the iridium (IV) / iridium (III) atomic ratio in the iridium-containing layer is in the range of 1.9 / 1.0 to 4.7 / 1.0, more preferably 2.5 / 1.0 to 4.7 / 1.0. The iridium (IV) / iridium (III) atomic ratio can be adjusted by the temperature of the heat treatment of the catalyst. Heat treatment of the catalyst at high temperatures favors high values of the iridium (IV) / iridium (III) ratio. Preferred temperatures for the heat treatment of the catalyst are also specified below.
[0038] The catalyst preferably does not contain metallic precious metals (such as platinum, palladium, iridium, rhodium, ruthenium, osmium, silver or gold). By metallic precious metals is meant precious metals in the zero oxidation state. The absence of metallic precious metals can be verified by XPS.
[0039] Optionally, the iridium-containing coating may also contain ruthenium in the +3 oxidation state (Ru(III)) and / or the +4 oxidation state (Ru(IV)).
[0040] Suitable support materials to which the iridium-containing coating can be applied are known to those skilled in the art. For example, the support material is an oxide of a transition metal (e.g., titanium oxide (e.g., TiO2), zirconium oxide (e.g., ZrO2), niobium oxide (e.g., Nb2O5), tantalum oxide (e.g., Ta2O5) or cerium oxide), an oxide of a main group metal (e.g., aluminum oxide such as Al2O3), SiO2 or a mixture of two or more of the aforementioned support materials. In a preferred embodiment, the support material is titanium oxide.
[0041] The support material is typically a granular support material.
[0042] For electrochemical activity of the catalyst, it may be advantageous to avoid longer heat treatments at high temperatures, in other words, if the loaded support material is dried at mild temperatures and subsequent high temperature calcination of the material is omitted, or at least the duration of the heat treatment at higher temperatures is kept relatively short, the material exhibits high levels of catalytic activity in the oxygen evolution reaction under acidic conditions.
[0043] For example, during its preparation, the catalyst is not subjected to a heat treatment at a temperature exceeding 250° C. for a period exceeding one hour.
[0044] For example, during its preparation, the catalyst is dried at a temperature of at most 250° C., more preferably at most 200° C., and is not subjected to any further heat treatment after drying.
[0045] If the catalyst is not subjected to a thermal post-treatment during its manufacture, this may result in a catalyst with a rather low electrical conductivity. In the anode of the water electrolysis cell, the catalyst-containing coating present on the membrane may, for example, be adjacent to a porous transport layer (PTL). The porous transport layer may be made, for example, of titanium, and a thin oxide layer may form on the metal. If the catalyst has a rather low electrical conductivity, this may result in an undesirable increase in the contact resistance at the interface between the catalyst-containing coating and the porous transport layer, and thus may adversely affect the efficiency of the water electrolysis cell. The contact resistance between the catalyst-containing coating and the titanium porous transport layer may be reduced, for example, when a noble metal (e.g. platinum) is applied to the porous transport layer, whereby the catalyst-containing coating is adjacent to this metallic platinum layer.
[0046] It may be advantageous if the catalyst is subjected to a thermal post-treatment at some elevated temperature during its manufacture in order to improve the electrical conductivity of the catalyst and thus avoid the application of a noble metal layer to the porous transport layer in the water electrolysis cell.
[0047] An advantageous compromise between sufficiently high electrical conductivity and high electrochemical activity of the catalyst can be achieved, for example, if during its preparation the catalyst is subjected to a heat treatment at a temperature above 250° C., for example >250° C. to 550° C., more preferably 300° C. to 450° C., even more preferably 300° C. to 380° C. The heat treatment can be carried out, for example, in an oxygen-containing atmosphere. The heat treatment is carried out, for example, for a period of at least 1 hour, but preferably not more than 3 hours. As a result of this heat treatment (preferably 300° C. to 450° C., even more preferably 300° C. to 380° C.), the electrical conductivity of the catalyst can be significantly increased (for example, 50-fold to 100-fold) compared to the non-heat-treated catalyst, while the electrochemical activity is only moderately reduced (for example, 1.5-fold to 2-fold).
[0048] For example, the catalyst, during its preparation, is not subjected to a heat treatment at a temperature exceeding 360° C. for a period of more than 60 minutes.
[0049] The particulate catalyst preferably comprises a core-shell structure, with the support material forming the core and the iridium-containing coating forming the shell. Preferably, the core is completely surrounded by the shell.
[0050] According to a third aspect of the present invention, the above object is achieved by -2m 2 / g~<10m 2 / g, more preferably 2m 2 / g~9m 2 / g; and a support material comprising a BET surface area in the range of an iridium-containing coating provided on a support material and containing iridium oxide, iridium hydroxide, or iridium oxide hydroxide, or a mixture of at least two of these iridium compounds; A granular catalyst comprising: The catalyst comprises an iridium content of 5% to 20% by weight, more preferably 5% to 14% by weight. This is achieved by a granular catalyst.
[0051] For suitable support materials, reference can be made to the above. For example, the support material is an oxide of a transition metal (for example titanium oxide (for example TiO2), zirconium oxide (for example ZrO2), niobium oxide (for example Nb2O5), tantalum oxide (for example Ta2O5) or cerium oxide), an oxide of a main group metal (for example aluminum oxide such as Al2O3), SiO2 or a mixture of two or more of the aforementioned support materials. In a preferred embodiment, the support material is titanium oxide. The support material is usually a granular support material.
[0052] The above description can also be referred to for the preferred properties of the iridium-containing coating. The iridium-containing coating preferably contains iridium oxide hydroxide. In addition to oxide anions, iridium oxide hydroxide also contains hydroxide anions and can be represented, for example, by the following formula: IrO(OH)x, where 1≦x<2. For example, in the iridium-containing coating, the atomic ratio of iridium (IV) to iridium (III) determined by X-ray photoelectron spectroscopy (XPS) is at most 4.7 / 1.0. For example, the iridium (IV) / iridium (III) atomic ratio in the iridium-containing layer is in the range of 1.0 / 1.0 to 4.7 / 1.0. This can further improve the electrochemical activity of the catalyst. To achieve an advantageous compromise between high electrochemical activity and high electrical conductivity, it may be preferred that the iridium(IV) / iridium(III) atomic ratio in the iridium-containing layer ranges from 1.9 / 1.0 to 4.7 / 1.0, more preferably from 2.5 / 1.0 to 4.7 / 1.0. The iridium(IV) / iridium(III) atomic ratio can be adjusted by the temperature of the heat treatment of the catalyst.
[0053] Also with regard to the catalyst according to the third aspect of the invention, an advantageous compromise between sufficiently high electrical conductivity and high electrochemical activity of the catalyst can be achieved, for example, if during its preparation the catalyst is subjected to a heat treatment at a temperature of more than 250°C, such as >250°C to 550°C, more preferably 300°C to 450°C, even more preferably 300°C to 380°C.
[0054] Also, the catalyst according to the third aspect of the present invention preferably does not contain metallic precious metals (platinum, palladium, iridium, rhodium, ruthenium, osmium, silver, gold, etc.). By metallic precious metals is meant precious metals in the zero oxidation state. The absence of metallic precious metals can be verified by XPS.
[0055] The present invention also relates to a method for producing the above-mentioned particulate catalyst, wherein an iridium-containing coating containing iridium oxide, iridium hydroxide or iridium oxide hydroxide is deposited on a support material.
[0056] Deposition of the iridium-containing coating on the support material is carried out, for example, by a wet chemical process in which iridium oxide, iridium hydroxide or iridium oxide hydroxide is applied to the particulate support material under alkaline conditions and, optionally, by a thermal post-treatment.
[0057] Alternatively, the iridium-containing coating can be deposited on the support material by spray pyrolysis.
[0058] For example, the catalyst is prepared using the following method. - in an aqueous medium containing an iridium compound, an iridium-containing solid is deposited on a support material at a pH of ≥ 9, The support material loaded with the iridium-containing solid is separated from the aqueous medium and optionally subjected to a heat treatment.
[0059] The carrier material to be coated is, for example, present in a dispersed form in an aqueous medium. The aqueous medium contains an iridium compound that can be precipitated as an iridium-containing solid under alkaline conditions. Such iridium compounds are known to those skilled in the art. It is preferably an iridium (IV) or iridium (III) compound.
[0060] As already mentioned, the layer thickness can be adjusted by the amount of iridium oxide, iridium hydroxide or iridium oxide hydroxide deposited on the support material and by the BET surface area of the support material: the higher the BET surface area of the support material for a given amount of applied iridium oxide, iridium hydroxide or iridium oxide hydroxide, the smaller the layer thickness of the iridium-containing coating.
[0061] With regard to the BET surface area of the support material, reference can be made to the above description. The BET surface area of the support material is preferably greater than 2 m 2 / g~40m 2 / g, more preferably 2m 2 / g~<10m 2 / g, and even more preferably 2m2 / g~9m 2 / g.
[0062] Suitable iridium(III) or iridium(IV) compounds that precipitate as solids under alkaline conditions in aqueous solution are known to those skilled in the art. For example, iridium(III) or iridium(IV) compounds may be salts (e.g., iridium halides such as IrCl3 or IrCl4; iridium halides in which the anion is chloride, such as IrCl6; 2- iridium nitrate or iridium acetate), or an iridium-containing acid such as H2IrCl6. In a preferred embodiment, the aqueous medium contains an iridium(IV) halide, in particular Ir(IV) chloride.
[0063] Optionally, ruthenium (III) and / or ruthenium (IV) compounds may also be present in the aqueous medium. This allows deposition of iridium-ruthenium hydroxide oxide on the support material. When a ruthenium precursor compound is present in the aqueous medium, it may be, for example, a Ru(III) or Ru(IV) salt, such as a halide, nitrate or acetate.
[0064] For depositing the iridium-containing solid on the support material, the aqueous medium preferably has a pH value of ≧10, more preferably ≧11. For example, the aqueous medium has a pH value of 9-14, more preferably 10-14, or 11-14.
[0065] The aqueous medium typically contains at least 50% by volume water, more preferably at least 70% by volume, or even at least 90% by volume.
[0066] To deposit the iridium-containing solid on the support material, the temperature of the aqueous medium is, for example, 40°C to 100°C, more preferably 60°C to 80°C.
[0067] The support material can be dispersed (e.g. at room temperature) in an aqueous medium that already contains one or more iridium(III) and / or iridium(IV) compounds, but has a pH of <9. The pH of the aqueous medium is then increased to a value of ≥9 by addition of a base, and optionally the temperature of the aqueous medium is also increased until an iridium-containing solid is deposited on the support material via a precipitation reaction. Alternatively, it is also possible, for example, to disperse the support material in an aqueous medium that does not yet contain iridium compounds, and only add the iridium(III) and / or iridium(IV) compounds to the aqueous medium after setting a suitable pH value and, optionally, a specific precipitation temperature.
[0068] Insofar as ruthenium(III) and / or ruthenium(IV) compounds are also present in the aqueous medium, the solid applied by precipitation onto the support material contains, in addition to iridium, further ruthenium. The atomic ratio of iridium to ruthenium can, for example, be in the range of 90 / 10 to 10 / 90.
[0069] Separation of the iridium-containing solid-loaded support material from the aqueous medium is carried out by methods known to those skilled in the art (eg, by filtration).
[0070] The carrier material loaded with the iridium-containing solid is dried. The dry iridium-containing solid present on the carrier material is, for example, iridium hydroxide oxide. In addition to oxide anion, iridium hydroxide oxide also contains hydroxide anion, and can be represented, for example, by the following formula: IrO(OH)x, where 1≦x<2.
[0071] The temperature and duration of the heat treatment can be used to control whether iridium oxide, iridium hydroxide, or iridium oxide hydroxide is present in the coating present on the support material. High temperatures and long heat treatment times favor the formation of iridium oxide.
[0072] As already explained above, if longer heat treatments at high temperatures are avoided during the preparation of the catalyst, this may be advantageous for the electrochemical activity of the catalyst, in other words, if the loaded support material is dried at mild temperatures and a subsequent high-temperature calcination of the material is omitted, or at least the duration of the heat treatment at higher temperatures is kept relatively short, this material will show a high level of catalytic activity in the oxygen evolution reaction under acidic conditions.
[0073] For example, in the present method, the coated support material is not subjected to a heat treatment at a temperature above 250° C. for a period of time greater than 1 hour. For example, in the present method, the coated support material is not subjected to a heat treatment at a temperature above 200° C. for a period of time greater than 30 minutes.
[0074] For example, the coated support material is dried at a temperature of up to 250° C., more preferably up to 200° C., and is not subjected to any further heat treatment after drying.
[0075] As already explained above, the electrical conductivity of the iridium-containing coating present on the support material, and therefore the electrical conductivity of the catalyst, can be improved if the thermal post-treatment is carried out at a somewhat higher temperature. An advantageous compromise between sufficiently high electrical conductivity and high electrochemical activity of the catalyst can be achieved, for example, if the coated support material is subjected to a thermal treatment at a temperature of more than 250°C, for example >250°C to 550°C, more preferably 300°C to 450°C, even more preferably 300°C to 380°C. The thermal treatment can be carried out, for example, in an oxygen-containing atmosphere. The thermal treatment is carried out, for example, for a period of at least 1 hour, but preferably not more than 3 hours.
[0076] The present invention further relates to a granular catalyst obtainable according to the above process.
[0077] The present invention further comprises: a catalyst as described above, - ionomers, in particular ionomers containing sulfonic acid groups (e.g. fluorinated ionomers containing sulfonic acid groups); The present invention relates to a composition comprising:
[0078] Suitable ionomers are known to those skilled in the art.For example, sulfonic acid group-containing fluorinated ionomers are copolymers that contain fluoroethylene (e.g., tetrafluoroethylene) and sulfonic acid group-containing fluorovinyl ether (e.g., sulfonic acid group-containing perfluorovinyl ether) as monomers.An overview of these ionomers can be found, for example, in the following publications: A. Kusoglu and AZ Weber, Chem.Rev., 2017, 117, p.987-1104.
[0079] The composition is, for example, an ink containing a liquid medium in addition to a catalyst and an ionomer. The liquid medium contains, for example, one or more short-chain alcohols (for example, methanol, ethanol, or n-propanol, or a mixture of at least two of these alcohols). The catalyst is present in the ink at a concentration of, for example, 5% to 60% by weight, more preferably 10% to 50% by weight or 20% to 40% by weight. The ionomer is present in the ink at a concentration of, for example, 5% to 50% by weight, more preferably 10% to 30% by weight.
[0080] The composition can also exist as a solid, for example, the anode of a water electrolysis cell contains the composition.
[0081] The present invention further relates to the use of said catalyst or said composition as an anode for water electrolysis, wherein the oxygen evolution reaction takes place at the anode, and the water electrolysis is preferably PEM water electrolysis, i.e. the oxygen evolution reaction takes place preferably under acidic conditions.
[0082] Measurement method Within the context of the present invention, the following measurement methods were used:
[0083] Average thickness of the iridium-containing coating on the carrier material The average thickness of the iridium-containing coating on the support material was determined by TEM (transmission electron microscopy).
[0084] A few μg of the material to be investigated were suspended in ethanol. A drop of the suspension was then pipetted onto a perforated carbon film-coated Cu platelet (Plano, 200 mesh) and allowed to dry. Measurements of the layer thickness were carried out at a magnification of 500,000 times. By parallel EDX elemental analysis of the elements (e.g. Ti) and Ir present in the support material, the TEM images show which regions on the support material particles contain iridium.
[0085] The thickness of the iridium-containing coating was determined on at least two TEM images, in each case at least five points on the TEM image. Each TEM image shows several particles. The arithmetic mean of these layer thicknesses gave the average thickness of the iridium-containing coating.
[0086] The relative standard deviation from the mean layer thickness, SD, sometimes called the coefficient of variation rel As is known, the percentage is given by the following relationship: SD rel = [SD / M] × 100 (In the formula, M is the average layer thickness, expressed in nm; SD is the standard deviation from the mean layer thickness, expressed in nm).
[0087] The (absolute) standard deviation, expressed in nm, is given, as is known, by the square root of the variance.
[0088] Iridium content of catalyst The iridium content and, if present, the ruthenium content, are determined by optical emission spectrometry with inductively coupled plasma (ICP-OES).
[0089] BET surface area The BET surface area was determined according to the BET theory (multipoint method, ISO9277:2010) at 77 K using nitrogen as the adsorbate.
[0090] Atomic ratio of Ir(IV) to Ir(III) The relative proportion of Ir atoms in oxidation state +4 versus Ir atoms in oxidation state +3, and thus the Ir(IV) / Ir(III) atomic ratio in the supported iridium hydroxide oxides, was determined by X-ray photoelectron spectroscopy (XPS). This ratio is determined by a corrected asymmetric Lorentzian peak fit with Shirley background in the detailed spectrum of the Ir(4f) doublet (BE 75-55 eV, Al-kα source). Furthermore, the presence of IrOH species in the detailed spectrum of O(1s) (BE about 531 eV, Al-kα source) is also detected by an asymmetric peak fit (Shirley background, Gaussian-Lorentzian composite function with Gaussian content 30%). The corresponding procedure is described, for example, in Abbott et al., Chem. Mater., 2016, 6591-6604.
[0091] XPS analysis can also be used to determine whether iridium(0) is present in the composition.
[0092] The present invention will now be described in more detail with reference to the following examples. EXAMPLES
[0093] Invention Example IE1 27.80 g of iridium(IV) chloride (IrCl4 hydrate, Heraeus Deutschland GmbH & Co. KG) was dissolved in 4000 mL of water at room temperature. Then, 29.94 g of TiO2 (DT20, Tronox, BET surface area: 20 m 21000g / g of iridium-containing solid was added. The pH was adjusted to 10.3 by adding NaOH. The aqueous medium was heated to 70°C and the pH was adjusted to 11. The aqueous medium was stirred at 70°C overnight. The pH was maintained at >11.0. The TiO2 support material loaded with iridium-containing solid was filtered off, washed and dried. Thermal post-treatment was carried out at 350°C for 1 h in an oxygen-containing atmosphere. The catalyst comprises a core-shell structure. XPS analysis showed that the iridium-containing coating present on the support material is iridium oxide hydroxide. Ir(IV) / Ir(III) ratio: 4.0:1.0.
[0094] Invention Example IE2 64.59 g of iridium(IV) chloride (IrCl4 hydrate, Heraeus Deutschland GmbH & Co. KG) was dissolved in 2500 mL of water at room temperature. Then, 53.15 g of TiO2 (DT30, Tronox, BET surface area: 30 m 2 1000g / g) was added. The pH was adjusted to 9.0 by adding NaOH. The aqueous medium was heated to 70°C and the pH was adjusted to 9.2. The aqueous medium was stirred at 70°C overnight. The pH was maintained at >9.0. The TiO2 support material loaded with iridium-containing solids was filtered off, washed and dried. Thermal post-treatment was carried out at 350°C for 1 h in an oxygen-containing atmosphere. The catalyst comprises a core-shell structure. XPS analysis showed that the iridium-containing coating present on the support material is iridium oxide hydroxide. Ir(IV) / Ir(III) ratio: 3.9:1.0.
[0095] Invention Example IE3 9.23 g of iridium(IV) chloride (IrCl4 hydrate, Heraeus Deutschland GmbH & Co. KG) was dissolved in 1000 mL of water at room temperature. Then, 44.85 g of TiO2 (DT-X5, Tronox, BET surface area: 5 m 21000g / g) was added. The pH was adjusted to 9.0 by adding NaOH. The aqueous medium was heated to 70°C and the pH was adjusted to 9.2. The aqueous medium was stirred at 70°C overnight. The pH was maintained at >9.0. The TiO2 support material loaded with iridium-containing solids was filtered off, washed and dried. Thermal post-treatment was carried out at 350°C for 1 h in an oxygen-containing atmosphere. The catalyst comprises a core-shell structure. XPS analysis showed that the iridium-containing coating present on the support material is iridium oxide hydroxide. Ir(IV) / Ir(III) ratio: 4.6:1.0.
[0096] Comparative example CE1 48.35 g of iridium(IV) chloride (IrCl4 hydrate, Heraeus Deutschland GmbH & Co. KG) was dissolved in 4000 mL of water at room temperature. Then, 51.9 g of TiO2 (Activ G5, Evonik, BET surface area: 150 m 2 1000g / g) was added. The pH was adjusted to 11.2 by adding NaOH. The aqueous medium was heated to 70°C and the pH was adjusted to >11. The aqueous medium was stirred at 70°C overnight. The pH was maintained at >11. The TiO2 support material loaded with iridium-containing solids was filtered off, washed and dried. A thermal post-treatment was carried out at 350°C for 1 hour in an oxygen-containing atmosphere. Isolated iridium-containing islands are present on the support material. XPS analysis showed that the isolated iridium-containing islands present on the support material contain iridium oxide hydroxide.
[0097] The iridium content of the catalysts and the average layer thickness of the iridium-containing coating present on the support material are summarized in Table 1 below.
[0098] Table 2 summarizes the BET surface areas of the support materials. In addition, Table 2 shows the BET surface area of the support material for each of the samples based on the associated BET surface area of the support material, as shown in the following relationship: (1.505(g / m 2 )×BET) / (1+0.0176(g / m 2 )×BET)≦Ir-G≦(4.012(g / m 2 )×BET) / (1+0.0468(g / m2 )×BET) is used to calculate the claimed iridium content range. In the inventive samples IE1, IE2 and IE3, the BET surface area of the support material and the iridium content of the catalyst are matched to one another such that the inventive relationship is satisfied. In the comparative material CE1, an iridium content that is too low in relation to the BET surface area of the support material is used. [Table 1]
[0099] For samples IE1 to IE3, the relative standard deviation of the average thickness of the iridium-containing coating is up to 20%. [Table 2] (1) (1.505(g / m 2 )×BET) / (1+0.0176(g / m 2 )×BET)≦Ir-G≦(4.012(g / m 2 )×BET) / (1+0.0468(g / m 2 )×BET)
[0100] Preparation of coating film and activity measurement The catalytic materials prepared in Examples IE1, IE2, IE3 and CE1 were used to prepare a coating membrane. For this purpose, the catalytic materials of Examples IE1, IE2, IE3 and CE1 were dispersed in an ink and applied to a membrane containing a sulfonic acid group-containing fluorinated polymer to form an anode.
[0101] The coating was achieved by a method called the decal method, in which a PTFE transfer film was transferred onto a polymer membrane (Nafion 117, 178 μm, Chemours). The coating of the PTFE film was performed using a Mayer bar coating machine. 2 A decal was punched out of the dried layer and pressed onto the polymer film under pressure (2.5 MPa) and temperature (155° C.). The loading was determined by weighing the PTFE before and after the transfer process.
[0102] For each of the coatings, the cell voltage was determined as a function of current density.
[0103] The test procedures for IE1, IE2, IE3 and CE1 were identical and were performed in an automated manner in an in situ measurement configuration. The current-voltage regulation was controlled using a potentiostat and booster (Metrohm Autolab PGSTAT302N and Booster 10A). After a warm-up phase and a conditioning step, galvanostatic polarization curves were performed at a cell temperature of 80° C. and a current of 0.01 A / cm. 2 ~2.00A / cm 2 At each current point, the cell voltage corresponding to the average value over 10 seconds after equilibration was determined. Figure 1 shows the measurement curves (cell voltage as a function of current density for IE1, IE2, IE3 and CE1). Figure 2 also shows the relevant range increase for IE1, IE2 and IE3 from Figure 1. In parallel, the high frequency resistance was determined by electrochemical impedance spectroscopy measurements at specific current points, so that the cell resistance could be corrected (IR free). These curves are not shown.
[0104] The results are summarized in Table 3. [Table 3]
[0105] The results show that the catalyst according to the invention has a very low surface-based iridium loading (1 cm of the coated membrane surface). 2 It is shown that this makes it possible to produce anodes having a content of less than 0.30 mg of iridium per cubic millimeter and which nevertheless have a very high electrochemical activity. [Brief description of the drawings]
[0106] [Figure 1] FIG. 1 shows the measurement curves (cell voltage as a function of current density for IE1, IE2, IE3 and CE1). [Diagram 2]FIG. 2 shows the increase in the relevant ranges of IE1, IE2 and IE3 from FIG.
Claims
1. a support material, - provided on said carrier material, - containing iridium oxide, iridium hydroxide or iridium oxide-hydroxide or a mixture of at least two of these iridium compounds, -having an average layer thickness in the range of 1.5 nm to 5.0 nm Iridium-containing coatings and A granular catalyst for oxygen evolution reaction in acidic water electrolysis, comprising: The catalyst comprises an iridium content of up to 50% by weight, the iridium-containing coating has an iridium(IV) / iridium(III) atomic ratio, as determined by X-ray photoelectron spectroscopy (XPS), in the range of 1.9 / 1.0 to 4.7 / 1.0; Granular catalyst.
2. 2. The granular catalyst of claim 1, wherein the iridium content of the catalyst is up to 40% by weight.
3. The BET surface area of the support material is 2 m 2 / g to 40m 2 The granular catalyst according to claim 1 or 2, wherein the molecular weight of the granular catalyst is 1000 or more.
4. -2m 2 / g to <10m 2 / g; and an iridium-containing coating provided on said support material and containing iridium oxide, iridium hydroxide or iridium oxide hydroxide or a mixture of at least two of these iridium compounds; A granular catalyst for oxygen evolution reaction in acidic water electrolysis, comprising: The catalyst comprises an iridium content of 5% to 20% by weight. Granular catalyst.
5. The iridium content of the catalyst is such that: (1.705(g / m 2 )×BET) / (1+0.0199(g / m 2 )×BET)≦Ir-G≦(3.511(g / m 2 )×BET) / (1+0.0410(g / m 2 )×BET) (Wherein, BET is m 2 / g and Ir-G is the iridium content of the catalyst, expressed in wt.%. The granular catalyst according to claim 3 or 4, which satisfies the above.
6. A granular catalyst according to any one of claims 1 to 5, wherein the iridium-containing coating has an average layer thickness of from 1.5 nm to 4.0 nm.
7. 7. The granular catalyst according to any one of claims 1 to 6, wherein the granular catalyst comprises a core-shell structure, in which the support material forms a core and the iridium-containing coating forms a shell.
8. 8. A granular catalyst according to claim 1, wherein the iridium is present exclusively as iridium in the +3 oxidation state (iridium(III)) and / or as iridium in the +4 oxidation state (iridium(IV)).
9. The support material is selected from the group consisting of transition metal oxides, main group metal oxides, SiO 2 or a mixture of two or more of the aforementioned support materials.
10. 10. The particulate catalyst according to claim 9, wherein the support material is titanium oxide.
11. A process for producing a granular catalyst according to any one of claims 1 to 10, wherein an iridium-containing coating containing iridium oxide, iridium hydroxide or iridium oxide hydroxide is deposited on a support material.
12. 12. The method of claim 11, wherein the particulate catalyst is subjected to a heat treatment at a temperature above 250°C.
13. - a granular catalyst according to any one of claims 1 to 10, -Ionomer and A composition comprising:
14. Use of the granular catalyst according to any one of claims 1 to 10 or the composition according to claim 13 as an anode for water electrolysis.
Citation Information
Patent Citations
Electrocatalyst composition comprising noble metal oxide supported on tin oxide
CN109906287A
Noble metal oxide catalyst for water electrolysis
JP2007514520A
Electrocatalyst composition comprising a noble metal oxide supported on tin oxide
JP2020500692A
Catalyst for the oxygen evolution reaction during water electrolysis
JP2022540820A
Precious metal oxide catalyst for water electrolysis
KR1020060100404A